Sistem Informasi Klasifikasi Minat Siswa Terhadap Ekstrakurikuler Untuk Pembinaan Lomba Dengan Metode K-Means Clustering - Ahmad Fanani; Siti Aminah; Febry Eka Purwiantono (LPPM UBHINUS MALANG, 2023)
Extracurricular activities at MI (Madrasah Ibtidaiyah) As – Shodiq are only used for activities outside normal school hours to fill out report cards, but problems arise. in the competition is not optimal. With the existing problems, it is expected that the information system built using the website combined with the k-means clustering method can solve the existing problems. By referring to the values ​​in the report cards and daily values, they become parameters for the k-means clustering method. In this study using the waterfall methodology, in the waterfall methodology there are various stages, such as requirements analysis, design, development and testing. This research aims to classify students in extracurricular classes which will then be fostered to maximize extracurricular activities. So, based on the results of research conducted in the development of an information system in the form of a website combined with the k-means clustering method, it has been able to classify students into classes of subjects in extracurricular, so that teachers can foster students in each class long ago. to prepare for the competition. However, in the information system there are still some obstacles such as the time of calculating k-means and features that can be added for further research.